Total phenolic and flavonoid contents, antioxidant, antidiabetic and antiplasmodial activities of Garcinia forbesii King: A correlation study - Wairata, Johanis; Fadlan, Arif; Purnomo, Adi Setyo; Bakhtiar, M. Taher; Ersam, Taslim (King Saud University, 2021)
Garcinia forbesii King belongs to Clusiaceae is a source of secondary metabolites espe- cially xanthones with various biological activities. G. forbesii King is also known for its empirical use for malaria and diabetes. This study investigated the total phenolic and flavonoid contents, in vitro antioxidant, antidiabetic and antiplasmodial activities of four extracts attained from the stem bark of G. forbesii King. The total phenolic and flavonoid contents were determined by spec- trophotometric methods and antioxidant activity was evaluated by DPPH, ABTS, FRAP assays. In vitro antidiabetic activity was assessed by a-glucosidase and a-amylase assays and antiplasmodial activity was studied against chloroquine sensitive Plasmodium falciparum strain 3D7. The highest value of total phenolic (187.37 ± 0.06 mg GAE/g) and flavonoid (35.97 ± 0.02 mg QE/g) contents were recorded in n-hexane and methanolic extracts. n-Hexane extract showed the highest DPPH activity with IC50 of 8.12 ± 0.02 lg/mL. Ethyl acetate extract exhibited better scavenging ability for ABTS with IC50 of 3.88 ± 0.04 lg/mL. The FRAP assay showed better activity in methanol extract with an inhibition value of 73.68 ± 3.66 mM Fe2+/g. The strong inhibition against a- glucosidase and a-amylase were displayed by dichloromethane extract with IC50 of 35.13 ± 2.01 lg/mL and 4.83 ± 0.20 lg/mL. n-Hexane and methanol extracts showed significant antiplasmodialactivity with IC50 of 0.23 ± 0.01 lg/mL and 0.73 ± 0.01 lg/mL, respectively. The correlation anal- ysis indicated a positive relationship of total phenolic and flavonoid contents with antiplasmodial activity. The results revealed that n-hexane and methanol extracts could be used as a potential nat- ural antiplasmodial, while dichloromethane extract is a promising natural antidiabetic.